The effectiveness of loving massage to the descent of pain uterus the post partum mother in BPM â€œRâ€ and BPS â€œBâ€ Bukittinggi in 2017 - Oktriani, Tuti; Susanti, Evi; Sovia, Adlin Dewi (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
The puerperium is a period of change that the body needs for physical recovery, changes that occur during the puerperium sometimes cause uncomfortable during the puerperium, especially during contraction and will result in abdomen pain. Loving Massage is proven to provide comfort, reduce anxiety, divert the pain experienced and Loving Massage can also produce hormones in the body that can provide comfort to the mother of postpartum. The purpose of this research is to know the effect of technique Loving Massage changes in pain this postpartum mather in BPM â€œRâ€ and BPS â€œBâ€ Bukittinggi. This type of research is experimental research with pre-experimental design and design that one group pre-test-post-test. The total sample of 14 people with a purposive sampling technique. the collection of data through observation and data collection tools used were sheets of observation NRS. From the results obtained by researchers that the average scale of pain before Loving Massage is 4.93 and average pain scale after Loving Massage is 2.50.Â Test results T-Dependent is P value=0,0001 which means there is an influence technique Loving Massage to change pain in postpartum.